Hb Youngstown [β101(G3)Glu → Ala; HBB: c.305A > C]: An Unstable Hemoglobin Variant Causing Severe Hemolytic Anemia. (December 2014) - Edward, Heather L.; Pisani, Louis Almero Du; Rodriguez-Romero, Walter E.; Chaves-Villalobos, Jorge; Garcia-Quesada, Jonielle; Harris, Neil S.; Luo, Hong-Yuan; Steinberg, Martin H.; Forget, Bernard G.; Chui, David H.K.
Abstract Hb Youngstown is a rare hemoglobin (Hb) variant caused by substitution of glutamic acid with alanine at amino acid residue 101 of the β-globin chain as a result of an A > C transversion on the β-globin gene nucleotide sequences [β101(G3)Glu → Ala; HBB: c.305A > C]. We now report three patients from two different families, one from South Africa and the other from Costa Rica, who are heterozygous for this Hb variant. All three carriers had marked hemolysis, consistent with Hb Youngstown being a highly unstable variant. The substitution of glutamic acid, a large and negatively charged amino acid, with alanine, a small and non polar amino acid, in the interface of the α1- and β2-globin subunits might interfere with the transition between the oxy- and deoxyHb, and lead to Hb instability and hemolytic anemia.